Students' Emotional and Cognitive Competencies in Entrepreneurship Through Entrepreneurship Education - Sukomo; Heryati , Tati; Prawiranegara, Benny (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
Most students only focus on academic competence and need more entrepreneurial skills, making it challenging to develop potential outside the educational field and less ready to compete in the world of work. The purpose of this study is to analyze the role of entrepreneurship education at the vocational high school level in shaping students' emotional and cognitive competencies to enter the field of entrepreneurship. The data collection method used in this research is a questionnaire using a data collection instrument: a questionnaire sheet with a Likert scale. The subjects involved in the study were 500 vocational high school students taken from 3 schools. After the data was collected, it was analyzed using the structural equation model data analysis method to analyze the variables' contribution. The results of this study indicate that entrepreneurship education can contribute to students' emotional and cognitive competencies by increasing and decreasing entrepreneurial interest. The contribution of students' emotional and cognitive competencies directly influences attitudes and interest in entrepreneurship and student self-efficacy. Thus, students with emotional competence will be more interested in entrepreneurship and considered more ready to become entrepreneurs. This study provides implications for school stakeholders that moderate entrepreneurship education can shape students' competencies and cognition in entrepreneurship so that entrepreneurship education can be used as an alternative program in schools.